2013
DOI: 10.1007/s00280-013-2151-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study investigating the safety and pharmacokinetics of highly bioavailable curcumin (Theracurmin®) in cancer patients

Abstract: Repetitive systemic exposure to high concentrations of curcumin achieved by Theracurmin did not increase the incidence of adverse events in cancer patients receiving gemcitabine-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(141 citation statements)
references
References 39 publications
3
134
1
3
Order By: Relevance
“…Although the oral administration of 10 or 12 g of natural curcumin was safe in a previous clinical study (14), there is a possibility of unexpected side effects due to high plasma curcumin levels as a result of improvement of the absorption efficiency. Long-term administration of Theracurmin at a dose of 150 mg is safe and well-tolerated (24). Moreover, a 6-mo, ongoing clinical study using 180 mg of Theracurmin has so far indicated that Theracurmin at this dose is safe (Morimoto, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the oral administration of 10 or 12 g of natural curcumin was safe in a previous clinical study (14), there is a possibility of unexpected side effects due to high plasma curcumin levels as a result of improvement of the absorption efficiency. Long-term administration of Theracurmin at a dose of 150 mg is safe and well-tolerated (24). Moreover, a 6-mo, ongoing clinical study using 180 mg of Theracurmin has so far indicated that Theracurmin at this dose is safe (Morimoto, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The total curcumin content in each preparation was considered to be approximately equal without breaking the capsules. Theracurmin was reported to be used at 100-400 mg in patients with cancer or healthy elderly volunteers for chronic treatment in clinical studies, indicating that at least 400 mg of Theracurmin was safe (24)(25)(26)(27). Moreover, more than 10 phase 2 clinical trials are now ongoing using 180 mg of Theracurmin, and no signifi cant adverse effect has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most attractive and vital reason for the therapeutic use of curcumin is its superior safety profile. It has been demonstrated that curcumin has very low toxicity, even at very high doses (6). Nevertheless, native curcumin cannot reach the therapeutic target in a therapeutic concentration because of its low bioavailability.…”
mentioning
confidence: 99%